Velocity of small-scale auroral current systems over MAITRI, Antarctica in Jan 1997 - Elango, P.; Gudade, A.L.; Sankaran, S.; Dhar, Ajay; Rajaram, G. (2000)
In continuation of our earlier experiments operated at MAITRI, Antarctica, in Jan 1992, Jan 1995 and Jan 1996, to determine the velocity of disturbed-time overhead current systems, a similar experiment was conducted again in Jan 1997. Fluxgate magnetometers were operated at the three sites, MAITRI, DAKSHIN GANGOTRI, and FILCHNER FJELLA, recording daily variation (DV) and magnetic pulsations (MP) in the three orthogonal components X, Y and Z. the pulsations are recorded in the frequency band 33 m Hz i.e. their time-periods range from 30 sec. to 3000 sec. The auroral current systems while drift¬ing over the stations, leave signatures in the form of geomagnetic pulsations in the ground-based magnetometers, and the velocity of the current systems can be estimated from the time-lags in similar pulsations at the three stations using the inter-station distances. A velocity of 0.5 km/sec to 3 km/sec was obtained for conditions of moderate magnetic disturbance during the Jan. 1997 campaign at MAITRI and it tallies well with our earlier results.